Upaya Peningkatan Mutu Pendidikan Melalui Peran Komite - Tita Sandra; Saipul Annur; Afriantoni Afriantoni (Studia Manageria, 2023)
This article aims to describe efforts to improve the quality of education at one of the State MTs in Palembang through planning, implementation and the role of committees. The type of research used is descriptive qualitative research. The informants used in this research were the committee chair as the key informant, while the school principal, deputy principal, teaching staff and stakeholders as supporting informants. Data collection techniques use interviews, observation and documentation. Then analyzed through reduction, data presentation and verification using triangulation techniques. The results of this research are committee planning in the form of program determination and budget design, implementation in line with the school's vision and mission, as well as the role of the school committee as a consideration, supporter, controller and mediator. The efforts made by the committee are planning programs, actualizing programs, accommodating aspirations and communicating various policies. The implications of this research are the creation of an attitude of tolerance and mutual support for the same goal, and it is necessary to optimize the role of the school committee in order to improve the quality of education in schools.